The Effect of Speed-Reading Technique on Eleventh Graders’ Reading Skills - Rosa Widyaningtyas; Helta Anggia (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigated the effectiveness of speed-reading instruction employing authentic technology-themed text adopted from BreakingNewsEnglish.com in enhancing eleventh-graders’ vocational high reading skills, focusing on reading fluency and reading comprehension. This study implemented a quantitative quasi-experimental design conducting a non-equivalent control group pre-test and post-test format. There were 48 Pringsewu vocational eleventh-grade students participated in this research, assigned into an experimental group and a control group. The descriptive statistics and independent samples t-test were used to analyze the data collected. Findings in reading comprehension revealed a significant difference in reading comprehension, with the experimental group achieving greater scores compared to the control group. However, the control group demonstrated statistically higher reading speed scores rather than the experimental group. These results indicate that speed-reading instruction supported deeper comprehension but did not result in higher reading speed. The study concludes that speed-reading instruction is most effective when combined with comprehension-focused scaffolding and authentic digital materials. The findings highlight the interdependent connection between reading fluency and reading comprehension and emphasize the importance of balancing reading speed with meaningful understanding in vocational high school contexts.